2017
DOI: 10.1016/j.schres.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Altered fucosyltransferase expression in the superior temporal gyrus of elderly patients with schizophrenia

Abstract: Glycosylation is a post-translational modification that is an essential element in cell signaling and neurodevelopmental pathway regulation. Glycan attachment can influence the tertiary structure and molecular interactions of glycosylated substrates, adding an additional layer of regulatory complexity to functional mechanisms underlying central cell biological processes. One type of enzyme-mediated glycan attachment, fucosylation, can mediate glycoprotein and glycolipid cell surface expression, trafficking, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…This may suggest abnormalities of brain aging in schizophrenia that are consistent with atypical neurodevelopment in earlier stages of the disorder. As with the fucosyltransferase POFUT2, protein levels of FUT8 were found decreased in schizophrenia STG (Mueller et al, 2017), supporting the notion that glycan processing enzyme expression protein and/or mRNA levels demonstrate brain region-specific abnormalities in schizophrenia.…”
Section: Extracellular Matrix and Synaptic Remodelingsupporting
confidence: 58%
See 3 more Smart Citations
“…This may suggest abnormalities of brain aging in schizophrenia that are consistent with atypical neurodevelopment in earlier stages of the disorder. As with the fucosyltransferase POFUT2, protein levels of FUT8 were found decreased in schizophrenia STG (Mueller et al, 2017), supporting the notion that glycan processing enzyme expression protein and/or mRNA levels demonstrate brain region-specific abnormalities in schizophrenia.…”
Section: Extracellular Matrix and Synaptic Remodelingsupporting
confidence: 58%
“…B3GNT8, MGAT4A, and FUT8 are primarily localized to the Golgi apparatus, thus the opposite valence of protein and mRNA expression changes may be an indication that glycosylation alterations in schizophrenia stem from abnormalities of glycan or glycoprotein processing in the ER which the cell attempts to compensate for further along the processing pathway in the Golgi apparatus. While the expression of some other GlcNAcTases found to be abnormally transcribed in this study were found unchanged at the protein level (Kim et al, 2018;Kippe et al, 2015;Mueller et al, 2017), this does not preclude the possibility that PTMs or functional properties of normally-expressed enzymes may be impaired. The majority of enzymes examined in this report are themselves glycosylated; hence, the altered expression of these enzymes may not only affect the function of a variety of substrate proteins and lipids, but also the efficacy and kinetics of the enzyme-mediated glycosylation pathways in which they participate.…”
Section: Limitations and Conclusionmentioning
confidence: 55%
See 2 more Smart Citations
“…The investigator who performed western blots was blind to subject diagnosis until study completion, and the investigator who performed statistical analyses was blind to diagnosis during data collection. Sample sizes were determined a priori using a power calculation (β = 0.2, π = 0.8) based on prior assessments of glycosylation enzyme protein expression in our lab (Kippe et al, 2015;Mueller et al, 2017). Data analysis was performed using Prism 6.07 (GraphPad Software Inc., La Jolla, CA) and STATISTICA 7.1 (StatSoft Inc., Tulsa, OK).…”
Section: Discussionmentioning
confidence: 99%